menu search
brightness_auto
more_vert

The Boolean expression \(∼(p⇒(∼q))\) is equivalent to :

(a) p ^ q

(b)\( q⇒∼ p\)

(c) p v q

(d)  \((∼p)⇒q\)

thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike

1 Answer

more_vert
 
verified
Best answer

Correct option is A)  p^q 

Explaination::
\(∼(p⇒(∼q))\) 

as \({p⇒q \ is \ same \ as \ ∼p v q}\) 

we get \(∼((∼p) v(∼q)) = \)  p^q

 

thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike

Related questions

thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike
1 answer
thumb_up_off_alt 500 like thumb_down_off_alt 0 dislike
1 answer
thumb_up_off_alt 501 like thumb_down_off_alt 0 dislike
1 answer
thumb_up_off_alt 501 like thumb_down_off_alt 0 dislike
1 answer

5.2k questions

4.7k answers

75 comments

393 users

...